Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction

Novel, concise and efficient protocol for non-natural piperidine compounds - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Formal synthesis of L-altro-1-deoxynojirimycin, cis-3-hydroxypipecolic acid along with synthesis of (R)-piperidinol and a conceptually different advanced intermediate for non-natural piperidine alkaloids is reported from cis-butene-1,4-diol. The key reactions involved are Johnson-Claisen rearrangement, Sharpless asymmetric dihydroxylation, reductive lactamization and novel regioselective elimination.

Protecting group free and scalable approach towards total synthesis of (-)-venlafaxine - Chavan, Subhash P.; Pawar, Kailash P.; Garai, Sumanta (RSC Advances, 2014)
A protecting group free asymmetric total synthesis of (-)-venlafaxine is reported. The strategy employs Sharpless epoxidation and regio-selective epoxide ring opening by an in situ generated Gilman reagent as key steps. This paper reports a 53% overall yield in 6 steps for total synthesis of (-)-venlafaxine.

Total syntheses of D-allo-1-deoxynojirimycin and L-talo-1-deoxynojirimycin via reductive cyclization - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Synthesis of a polyhydroxypiperidine framework for L-talo-1-deoxynojirimycin and D-allo-1-deoxynojirimycin was achieved from L-tartaric acid by employing flash dihydroxylation and reductive lactamisation as the key steps.

Chirality induction and chiron approaches to enantioselective total synthesis of alpha-lipoic acid - Chavan, Subhash P.; Pawar, Kailash P.; Praveen, Ch; Patil, Niteen B. (Tetrahedron, 2015)
An efficient, short and convenient asymmetric synthesis of (R)-(+)-lipoic acid in seven steps from chiral hydroxy aldehyde with 32.5% overall yield is described. Synthesis of S and R enantiomers of a-lipoic acid from cis-1,4-butene diol derived chiral lactone is reported with 34 % overall yield. The present synthesis involves use of simple reaction conditions making it a convenient synthesis. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool; Chirality induction; enantioselective; Lipoic acid; sharpless asymmetric dihydroxylation

Enantioselective syntheses of (R)-pipecolic acid, (2R,3R)-3-hydroxypipecolic acid, beta-(+)-conhydrine and (-)-swainsonine using an aziridine derived common chiral synthon - Chavan, Subhash P.; Khairnar, Lalit B.; Pawar, Kailash P.; Chavan, Prakash N.; Kawale, Sanket A. (RSC Advances, 2015)
Concise total syntheses of (R)-pipecolic acid, (R)-ethyl-6-oxopipecolate, (2R, 3R)-3-hydroxypipecolic acid and formal syntheses of beta-(+)-conhydrine, (-)-lentiginosine, (-)-swainsonine and 1,2-di-epi-swainsonine have been accomplished starting from a common chiral synthon. The present strategy employs regioselective aziridine ring opening, Wittig olefination and RCM as the key chemical transformations.

Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid

Synthesis of 3-ethyl-4-metyl-1h,5-dihydro-2h-pyrrol-2-one by novel palladium(ii)-catalyzed cyclization and ring-closing metathesis - Chavan, Subhash P.; Pathak, Ashok B.; Pawar, Kailash P. (Synthesis-Stuttgart, 2015)
Synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one is described starting from commercially available allylamine and 4-methoxybenzylamine employing palladium-catalyzed cyclization or ring-closing metathesis as the key steps.
Keywords: antidiabetic; cyclization; glimepiride; lactams; metabolite; pyrrolinone; Ring-closing metathesis

Total synthesis of (R)-lipoic acid and (S)-lipoic acid via an Mn (III)-salen-catalyzed oxidative kinetic resolution - Purude, Abhijeet N.; Pawar, Kailash P.; Patil, Niteen B.; Kalkote, Uttam R.; Chavan, Subhash P. (Tetrahedron-Asymmetry, 2015)
The asymmetric synthesis of both the antipodes of alpha-lipoic acid is described. The total synthesis of racemic and asymmetric lipoic acid is achieved from propane 1,3-diol. This work reports the use of Mn (III)-salen-catalyzed oxidative kinetic resolution as the key step to obtain enantiomerically pure (R)- and (S)-lipoic acid. The undesired product formed during the resolution can be recycled to achieve the desired isomer. (C) 2015 Elsevier Ltd. All rights reserved.

Asymmetric total synthesis of L-allo-1-deoxynojirimycin - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P.; Chavan, Prakash N.; Khairnar, Lalit B. (Arkivoc, 2016)
Asymmetric total synthesis of L-allo-1-deoxynojirimycin (L-allo-DNJ) was achieved from cis-butene-1,4-diol by employing Sharpless asymmetric dihydroxylation, stereoselective flash dihydroxylation and ring enlargement reactions as key steps.
Keywords: diastereoselective flash dihydroxylation; ring-enlargement reaction; sharpless asymmetric dihydroxylation